SOCIO-GENDER ANALYSIS IN A STUDY VIDEO "KETIKA ISTRI LEBIH DARI SUAMI" TO NETIZENS COMMENTS ON THE INSTAGRAM ACCOUNT@ muhammadnuzuldzikri - RIMA PRAMITA JUMADI; Yuke Yolanda; Halliza (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
Instagram is one of the digital media that is widely accessed to get various kinds of information. One of them is da'wah content on the Instagram account@ muhammadnuzuldzikri. This account has a fairly large number of followers because it has interesting content. In this study, we used the ethnographic method by analyzing public response based on the comments of the viewers on the video "Ketika Istri Lebih Dari Suami". This study aims to determine the response from the audience. After being analyzed, it can be concluded that the video has various comments that raise pro opinions whereas the men agree more with the opinions in the video. While the contra opinions are more dominated by women.